2006
DOI: 10.1149/1.2257656
|View full text |Cite
|
Sign up to set email alerts
|

Growth of CdS:Cu Nanocrystals by Chemical Synthesis

Abstract: CdS:Cu nanocrystalline films were prepared by chemical bath on glass substrates at a deposition temperature of 80°C. Different Cu-doping levels were obtained by changing the volume of the Cu-reagent-solution into the CdS growing solution. X-ray diffraction ͑XRD͒ and optical absorption ͑OA͒ measurements were carried out to characterize the material. From the XRD patterns it is concluded that grains in undoped films grow in the wurtzite hexagonal phase, and in Cu-doped films they grow in the zinc blende cubic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…As expected, UCV has a similar dependence with IDs versus V [Ni 2+ ] ; this type of plot has been reported when Cu 2+ in CdS is either decreasing or increasing [6]. To the best of our knowledge, no dependence between IDs and GS has been found in theoretical approaches and experimental findings on doped and undoped nanocrystals reported [6,21,22]. Figure 9 exhibits the (111) interplanar distance (ID) as function of the average GS, and in inset the 1/GS versus unit cell volume (UCV) is displayed.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…As expected, UCV has a similar dependence with IDs versus V [Ni 2+ ] ; this type of plot has been reported when Cu 2+ in CdS is either decreasing or increasing [6]. To the best of our knowledge, no dependence between IDs and GS has been found in theoretical approaches and experimental findings on doped and undoped nanocrystals reported [6,21,22]. Figure 9 exhibits the (111) interplanar distance (ID) as function of the average GS, and in inset the 1/GS versus unit cell volume (UCV) is displayed.…”
Section: Resultssupporting
confidence: 81%
“…It can be seen for the PbSNi0, GS ∼32 nm, that the GS decreases for doped samples. The effect of the GS decrease by the doping effect has been reported in films of CdS doped with Cu 2+ by CBD [6]. A decrease in the degree of order of crystallites is expected to lead to enhanced growth of stable nuclei at the initial stages of growth, followed by impaired grain growth, and hence resulting in smaller grains in the nickel.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The intensity change in (200) peak, as shown in the inserted pattern, highlights the strong dependency of crystallization on the content of Cu. It has been reported that Cu in the chemical bath deposition may have different reaction kinetics in forming the chalcogenide phase so that the involvement of Cu precursor acts negatively in the sulfide formation[23][24][25].…”
mentioning
confidence: 99%